Comparison of the effect of guided visualization technique and cryotherapy on pain intensity during needle insertion into arterial–venous vessels of hemodialysis undergoing patients: A cross-over clinical trial - Zahra Ghazanfari; Saeed H. Teshnizi; Pooneh Yousefi; Aref Faghih (Journal of Education and Health Promotion)
BACKGROUND: End-stage renal disease patients experience pain during needle insertion each time they undergo vascular access. This pain is the most severe aspect of hemodialysis-related stress. Based on this, this study was conducted with the aim of the effect of guided visualization technique and cryotherapy on the intensity of pain when the needle enters the arterialvenous vessels in patients undergoing hemodialysis. MATERIALS AND METHODS: This cross-over clinical trial was conducted on 60 patients undergoing hemodialysis from September to December 2023. Patients were randomly assigned to three independent groups (n = 20 people per group). This study was conducted in three stages, during which each group received guided visualization, cryotherapy, and routine care (control) separately. Pain intensity was measured individually using the numerical rating scale at the end of each interventions. Data analysis was performed using data statistics (Stata) version 14 and Statistical Package for the Social Science version 26. RESULTS: The results showed that guided visualization significantly outperformed cryotherapy across all three groups and stages. Additionally, both guided visualization and cryotherapy significantly outperformed the control group in reducing pain following needle insertion in patients undergoing hemodialysis. CONCLUSION: Guided visualization can be used as a safe and secure method to reduce pain when the needle enters the arteriovenous fistula in patients undergoing hemodialysis. TRIAL REGISTRATION NUMBER: IRCT202308080590. (21/08/2023).